2018
DOI: 10.1021/acsanm.8b01804
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Nickel–Poly(vinylidene fluoride trifluoroethylene) Nanowires for Magnetoelectric Applications

Abstract: Magnetoelectric (ME) composite materials, in which the coupling between magnetostricitve and piezoelectric effects is achieved, are potential candidates for multifunctional devices where the interplay between electrical, magnetic and mechanical properties of these structures can be fully exploited. Nanostructured composites are particularly interesting due to the enhancement of ME coupling expected at the nanoscale. However, direct studies of ME coupling in nanocomposites by scanning probe techniques are rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Frequency shift Δf between peaks and troughs were used as an indication for the magnetization changes in the NFs, as developed by Boughey and Bai. 3,11 It is observed that Δf increases with the increase in poling voltage, indicating the high response of the ME coupling under high poling voltages. As shown in Figure 5C, the frequency shift (Δf 1 ) is about 0.6 kHz for non-poling NF (0 V), whereas after the NF was poled under 6 V, the frequency shift (Δf 2 ) was increased to 1.1 kHz, indicating the magnetization changed after an electric field poling in PFM mode.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Frequency shift Δf between peaks and troughs were used as an indication for the magnetization changes in the NFs, as developed by Boughey and Bai. 3,11 It is observed that Δf increases with the increase in poling voltage, indicating the high response of the ME coupling under high poling voltages. As shown in Figure 5C, the frequency shift (Δf 1 ) is about 0.6 kHz for non-poling NF (0 V), whereas after the NF was poled under 6 V, the frequency shift (Δf 2 ) was increased to 1.1 kHz, indicating the magnetization changed after an electric field poling in PFM mode.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure 5C, the frequency shift (Δf 1 ) is about 0.6 kHz for non-poling NF (0 V), whereas after the NF was poled under 6 V, the frequency shift (Δf 2 ) was increased to 1.1 kHz, indicating the magnetization changed after an electric field poling in PFM mode. According to the method used by Boughey 3 and Bai, 11 the magnetization (M i ) was considered to have a linear relation to the measured frequency shift (Δf i ) before and after electrical poling. This can be expressed by the following equation:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations